Penerapan Data Warehouse untuk Laporan Fact Finding pada PT Mitra Pinasthika Mulia - Hendyk Cendana Santoso; Silvia Rostianingsih; Leo Willyanto Santoso (Jurnal Infra, 2019)
PT Mitra Pinasthika Mulia uses the fact finding system to analyze the state of public relations within the company. But in making fact finding reports, companies still use manual methods namely by using Microsoft Excel. This causes the making of fact finding reports that are used to analyze public relations requires considerable time and labor.Therefore, the creation of a data warehouse for business intelligence programs is needed by the company PT Mitra Pinasthika Mulia in speeding up data processing and making fact finding reports that can help analyze public relations. This program helps reduce the time and labor needed to make fact finding reports. Data contained in reports and data warehouses in accordance with the wishes of the company. This program can be developed by adding the scope of data taken from each system of public relations found in the company PT Mitra Pinasthika Mulia.